Beyond State Recognition of Customary Forests: Initiating Agrarian Reform in Indigenous Peoples - Eko Cahyono; Arif Satria; Endriatmo Soetarto; Soeryo Adiwibowo; Didik Suhardjito (Departemen Sosiologi Universitas Gadjah Mada, 2025)
This article examines the socio-political dynamics of agrarian issues surrounding the recognition of customary forests in Kasepuhan Karang, Lebak Regency, Banten. The recognition of customary forests is interpreted by indigenous peoples as a political victory. The political policy of recognition provides opportunities for indigenous peoples to reclaim their customary lands that have been subjected to agrarian colonialism, although this is limited to the recognition of customary forest areas. The data presented is based on the author's periodic research, which was intensive during 2018 and 2019, and continued through various field studies in 2020, 2023, 2024, and early 2025. Field data was collected using qualitative methods, through direct observation, live-in, in-depth interviews with key informants, and focus group discussions. The findings of this research show that the state's recognition of customary forests is half-hearted, partial, and fragmentary, so that socio-agrarian conditions remain unchanged and the previous structure of agrarian inequality remains intact. The state unilaterally recognized only some of the proposed customary forests, while ignoring the social dynamics and changes in the Kasepuhan Karang community, which experienced social differentiation due to the concentration of land ownership. The ideas and recommendations proposed are to encourage agrarian reform in indigenous peoples. This is to ensure agrarian justice, which has been ignored by the existing political recognition model. Among the requirements for agrarian reform in indigenous peoples is interconnectivity between ecological aspects, tenure systems, and local socio-cultural aspects, so that its implementation is flexible and contextual, and certainly cannot be standardized.